МАТЕМАТИЧЕСКИЕ МОДЕЛИ ЧИСЛЕННОГО РЕШЕНИЯ КРАЕВЫХ ЗАДАЧ НЕСТАЦИОНАРНОЙ ТРЕХФАЗНОЙ ФИЛЬТРАЦИИ (Scientific journal of the Fergana State University, 2023)
The construction of an explicit / implicit scheme for the numerical solution of regional problems of non-stationary three-phase filtration is considered in the article